Virtual pretreatment patient‐specific quality assurance of volumetric modulated arc therapy using deep learning - SA Yoganathan (17760132) (2023)
Background Automatic patient‐specific quality assurance (PSQA) is recently explored using artificial intelligence approaches, and several studies reported the development of machine learning models for predicting the gamma pass rate (GPR) index only. Purpose To develop a novel deep learning approach using a generative adversarial network (GAN) to predict the synthetic measured fluence. Methods and materials A novel training method called “dual training,” which involves the training of the encoder and decoder separately, was proposed and evaluated for cycle GAN (cycle‐GAN) and conditional GAN (c‐GAN). A total of 164 VMAT treatment plans, including 344 arcs (training data: 262, validation data: 30, and testing data: 52) from various treatment sites, were selected for prediction model development. For each patient, portal‐dose‐image‐prediction fluence from TPS was used as input, and measured fluence from EPID was used as output/response for model training. Predicted GPR was derived by comparing the TPS fluence with the synthetic measured fluence generated by the DL models using gamma evaluation of criteria 2%/2 mm. The performance of dual training was compared against the traditional single‐training approach. In addition, we also developed a separate classification model specifically designed to detect automatically three types of errors (rotational, translational, and MU‐scale) in the synthetic EPID‐measured fluence. Results Overall, the dual training improved the prediction accuracy of both cycle‐GAN and c‐GAN. Predicted GPR results of single training were within 3% for 71.2% and 78.8% of test cases for cycle‐GAN and c‐GAN, respectively. Moreover, similar results for dual training were 82.7% and 88.5% for cycle‐GAN and c‐GAN, respectively. The error detection model showed high classification accuracy (>98%) for detecting errors related to rotational and translational errors. However, it struggled to differentiate the fluences with “MU scale error” from “error‐free” fluences. Conclusion We developed a method to automatically generate the synthetic measured fluence and identify errors within them. The proposed dual training improved the PSQA prediction accuracy of both the GAN models, with c‐GAN demonstrating superior performance over the cycle‐GAN. Our results indicate that the c‐GAN with dual training approach combined with error detection model, can accurately generate the synthetic measured fluence for VMAT PSQA and identify the errors. This approach has the potential to pave the way for virtual patient‐specific QA of VMAT treatments. Other Information Published in: Medical Physics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/mp.16567